Quality of Coconut Shell and Kusambi Liquid Smoke as Raw Materials for Processed Meat Smoking: Effect of Different Types of Filtration Adsorbents - Wibowo , Radya Setianto; Susilo , Agus; Rosyidi , Djalal (Current Perspectives in Agriculture and Food Science Vol. 5, 2023)
This research was conducted to learn more about the effect of filtration methods using various types of adsorbents on the quality of coconut shell liquid smoke and kusambi as raw materials for curing processed meat. Global meat consumption continues to grow at one of the highest rates compared to any other agricultural commodity due to increasing incomes, changing consumer preferences in many emerging economies, and lowering costs of meat production and meat prices. The research method used in this study was an experimental method, with a factorial Randomized Block Design (RBD). For each category of liquid smoke, there are three different types of treatment options: the first is an adsorbent-only treatment for liquid smoke, followed by zeolite adsorbent treatment, silica adsorbent treatment, and activated charcoal adsorbent treatment. Different liquid smoke types and adsorbent filtration methods had a very significant impact (P0.01) on the number of antioxidants, total acid, specific gravity, tar, phenol content, pH, salinity, TDS, total yield, L* and b* color, hedonic color, and smokey scent in the resulting liquid smoke, according to an analysis of variance. Analysis of variance revealed that the various liquid smoke varieties had no statistically significant impact (P0.05), but that the filtration process using various adsorbents had a highly significant impact (P0.01) on viscosity. Additionally, the analysis of variance revealed that the various liquid smoke varieties and the filtration of various adsorbents had no discernible impact (P0.05) on the final liquid smoke's hue a*. The antioxidant, total acid, specific gravity, tar, phenol content, pH, salinity, TDS, total yield, L* and b* color, hedonic color, and smoke aroma in the liquid smoke produced were all significantly affected by the various types of liquid smoke and how they were treated with adsorbents (P0.01). Although the various liquid smoke varieties did not significantly affect the final viscosity (P0.05), the various types of adsorbents used in the liquid smoke filtration procedure did significantly affect the viscosity (P0.01). The value of color a* or the reddish hue of the liquid smoke, however, were not significantly affected by the various types of liquid smoke or adsorbents used in the liquid smoke filtration process (P0.05).